Hubungan Senam Yoga Dengan Kesiapan Fisik Dan Psikologis Ibu Hamil Dalam Menghadapi Persalinan Di Kelas Antepartum Gentle Yoga Yogyakarta - Alfie Ardiana Sari; Dian Puspitasari (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Yoga in Pregnant, Physical and Psychological Of Preparation. During pregnancy will change physically and psychologically that will be experienced by a mother. These changes may cause discomfort, especially in the third trimester. Therefore pregnant women should receive care in pregnancy to be able to adapt to changes both physical and psychological. The purpose of care during pregnancy to prepare for childbirth which is physiological with the aim of mother and fetus will be born in a healthy state. One of the alternative ways to prepare for the physical and psychological mother in the face of labor is a pregnancy yoga exercises. The design of this study was a quantitative research with a cross-sectional study design. Population in this study were all pregnant women who do yoga exercises in Antepartum Gentle Yoga class at Hotel of Puri Artha Yogyakarta. The population in this study of 24 respondents. the instruments used questionnaires. The data were analyzed by bivariate. There was a significant correlation (p<0.001)between yoga exercise on physical and psychological preparation of pregnant women during labor. Yoga of pregnancy can help pregnant to prepare physically and psychology during labor